The Principal as a Manager: Improving Primary School Quality - Doni Saputra, Virma; Danim, Sudarwan (Universitas Ahmad Dahlan, 2025)
Background. This study aims to describe the principal’s managerial role in improving the quality of education at SDN 2 Srimulyo, Musi Rawas Regency, and to identify the supporting and inhibiting factors influencing its implementation. Methods. A qualitative descriptive method, with data collected through interviews, observations, and document analysis. Participants included the principal, teachers, school committee members, and students. Results. The findings reveal that the principal engages in data-driven planning, enhances teacher competencies through professional development programs, optimizes school resources, and promotes student character education. Key supporting factors include visionary leadership, active stakeholder involvement, and technology integration in school administration. However, significant challenges include limited financial resources, low teacher participation in decision-making, and inadequate infrastructure. Conclusion. This study underscores the critical role of the school principal in strategic and collaborative management to improve the quality of primary education.